2018
DOI: 10.2478/auoc-2018-0002
|View full text |Cite
|
Sign up to set email alerts
|

Human health risk assessment of heavy metals in soils and commonly consumed food crops from quarry sites located at Isiagwu, Ebonyi State

Abstract: In view of ensuring healthy agricultural foods for human consumption, this study assessed the human health risk implicated in selected heavy metals in some commonly consumed vegetables, tubers, nuts and fruits grown around the quarry sites at Ishiagu, Ebonyi State, Nigeria. Samples from agriculture area of Umudike, Abia State, Nigeria, constituted the control. The concentration of Mn, Zn, Fe, Cu, Cd, and Pb, were determined using atomic absorption spectrometry. The potential non-carcinogenic health risk for co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 22 publications
6
24
1
Order By: Relevance
“…Because the measured values for WEDIM for Cd in root vegetables from the R area were very close to the UL value for Cd, the consumption of these vegetal foodstuffs is highly likely to serve as a route for introducing Cd into the human body [ 16 , 56 , 60 ]. Our values were higher than those observed by Mincic in Kosovo [ 56 ], Onyedikachi in Nigeria [ 9 ], but close to those reported by Pypoian in Armenia [ 16 ], Llobet in Catalonia, Spain [ 22 ], Gebeyehu in Ethiopia [ 60 ], and Li and Zheng in selected industrial and mining areas from China [ 15 , 47 ]. We also observed that metal intakes via fruits were lower than those determined for vegetables, irrespective of analyzed site.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Because the measured values for WEDIM for Cd in root vegetables from the R area were very close to the UL value for Cd, the consumption of these vegetal foodstuffs is highly likely to serve as a route for introducing Cd into the human body [ 16 , 56 , 60 ]. Our values were higher than those observed by Mincic in Kosovo [ 56 ], Onyedikachi in Nigeria [ 9 ], but close to those reported by Pypoian in Armenia [ 16 ], Llobet in Catalonia, Spain [ 22 ], Gebeyehu in Ethiopia [ 60 ], and Li and Zheng in selected industrial and mining areas from China [ 15 , 47 ]. We also observed that metal intakes via fruits were lower than those determined for vegetables, irrespective of analyzed site.…”
Section: Resultssupporting
confidence: 80%
“…Heavy metals, such as iron (Fe), manganese (Mn), zinc (Zn), copper (Cu), nickel (Ni), cadmium (Cd) and lead (Pb) (hereinafter referred to as metals), are high-profile inorganic pollutants that once extracted from the natural environment and accumulated in plant foodstuffs can pose a serious hazard for both human and environmental health [ 1 , 2 , 3 , 4 ]. Sludges, solid wastes, fertilizers, waste waters, vehicular and industrial emissions, and many other industrial byproducts are major sources of soil contamination with metals [ 5 , 6 , 7 , 8 , 9 ]. There is compelling evidence for elevated metal uptake in people consuming food crops, vegetables and fruits grown on anthropically contaminated soils, and/or animal products (e.g., meat, milk, eggs) originating from these areas [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The fly ash was dried and mixed with cellulose to obtain pellets and was applied to the soil (about 200 t/ha). As it can be seen from Figure 5, the soil enrichment with heavy metals in rice crops did not exceed the upper control limits (in soil: 1500 ppm for Mn, 100 ppm for Cu and 300 ppm for Zn; in plant: 300 ppm for Mn, 50 ppm for Cu and 100 ppm for Zn) [31][32][33]. Thus, the soils treated with fly ash presented a slight enrichment with microelements, such as Zn, Mn and Cu, which are essential for plant growth.…”
Section: Environmental Risk Assessmentmentioning
confidence: 84%
“…It therefore follows that ingestion (oral) exposure to contaminants should not be the only criteria for assessing health risks. Other routes of human exposure such as gaseous intake (inhalation) and dermal deposition should be considered 38. The present study was aimed at determining the presence and levels of some heavy metals in soot air samples from Port Harcourt; an oil-rich city in Nigeria's Niger delta region.…”
Section: Introductionmentioning
confidence: 99%